The Cyder-Maker's Instructor, Sweet-Maker's Assistant, and Victualler's and Housekeeper's Director : In Three Parts - Chapman, Thomas (Wine cooper) (Salt Lake City, UT : Project Gutenberg, 2005)
"The Cyder-Maker's Instructor, Sweet-Maker's Assistant, and Victualler's and Housekeeper's Director" by Thomas Chapman is a comprehensive guide on the production and management of various fermented beverages, written during the mid-18th century. This instructional book, likely published in the 1760s, provides insights into the craft of making cyder, raisin wines, and malty beverages like beer and ale, offering practical instructions based on the author's extensive experience in the field. The book aims to inform both traders and households about the intricacies of fermentation and the care required to produce high-quality drinks. The content is organized into three main parts, each focusing on a different beverage type. In the first part, Chapman outlines the process of making cyder from fruit, detailing fermentation techniques, how to remedy common issues such as acidity and bad flavors, and methods to enhance the drink's appearance. The second part provides instructions for creating raisin wines, discussing the selection of fruit and the fermentation process. In the final part, he addresses brewing beer and ale, offering methods to fine and clarify these beverages, as well as how to create artificial yeast in case of shortages. Throughout the book, Chapman emphasizes the importance of following precise instructions in order to achieve successful results, making it a valuable resource for both novice and experienced makers of these traditional drinks. (This is an automatically generated summary.)
Release date is 2005-03-18
Produced by S.R.Ellison, Robert Cicconetti, and the Online Distributed Proofreading Team
Keywords: Liquors; Wine and wine making; Cider; Cooking (Cider)